SECONDARY TEACHERS’ AND STUDENTS’ PERCEPTIONS OF DISTANCE EDUCATION IN SCIENCE: FOCUS ON LEARNER-CENTERED, ACTION-ORIENTED, AND TRANSFORMATIVE LEARNING - Funa, Aaron A. (Trường Đại học Đà Lạt, 2024)
The shift from conventional, face-to-face classroom teaching to distance education is a complex process that brings various challenges. To better understand the impact of this transition, the researchers examined the perceptions of secondary science teachers (n = 42) and students (n = 137). Specifically, the study focused on evaluating learner-centered, action-oriented, and transformative learning – referred to as LCAOT learning – in science distance education. The researchers developed a 26-item, 4-point Likert scale questionnaire that was distributed online to the target respondents. Additionally, the researchers interviewed teachers and students and analyzed various documents, such as self-learning modules and learners’ activity sheets, to triangulate the survey data. The findings revealed that the principles of LCAOT learning were apparent in science distance education and exemplified through tools such as the Know, Want to Know, and Learned charts and personal journals. The study also revealed that teachers and students faced challenges during the transition to distance education, including inadequate equipment and poor internet connectivity. However, they responded to these challenges by using various means of communication, collaborating with peers, and exploring new roles and identities. The researchers recommend using the developed instrument and continuing to evaluate the effectiveness of teaching strategies employed in distance education in science, as well as further studies on the impact of LCAOT learning on students’ academic achievement.